Applications of nanomaterials in construction industry - Barbhuiya, Salim (IGI Publishers, 2014)
The application of nanomaterials in various applied field has gained worldwide recognition. Nanomaterials have the ability to manipulate the structure at nano-scale. This leads to the generation of tailored and multifunctional composites with improved mechanical and durability performance. Recognizing this, the construction industry recently has started to use a variety of nanomaterials. The use of these materials is found to improve various fundamental characteristics of construction materials including the strength, durability and lightness. In this chapter an attempt is made to review the use of various nanomaterials in cementitous system. This is followed by a discussion on the challenges related to their use. Finally, the strategies for using nanomaterials in construction industry for the next ten years have been identified.